2022
DOI: 10.1002/ppp3.10257
|View full text |Cite
|
Sign up to set email alerts
|

Botanical boom: A new opportunity to promote the public appreciation of botany

Abstract: Societal Impact Statement Plants are indispensable to life on Earth. Securing our future requires protecting plant biodiversity and the development of climate‐resilient crops. Activities fostering public appreciation of plant science, and promoting plant‐related professions, are therefore critical. These efforts can be hindered by plant awareness disparity, manifesting as difficulty in recognizing the presence and importance of plants. However, interest in plants as a hobby and as lifestyle elements has rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 53 publications
0
18
0
1
Order By: Relevance
“…Despite the success of synthetic drugs in modern medicine over the past century, statistics indicate that plant-based remedies meet the healthcare needs of nearly 80% of the world population, especially in rural areas (Bodeker et al, 2005;Burke et al, 2022). At the same time, there is also a growing interest world over in the use of traditional medical systems, which are vast repositories of plant-based medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the success of synthetic drugs in modern medicine over the past century, statistics indicate that plant-based remedies meet the healthcare needs of nearly 80% of the world population, especially in rural areas (Bodeker et al, 2005;Burke et al, 2022). At the same time, there is also a growing interest world over in the use of traditional medical systems, which are vast repositories of plant-based medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Framing personal narratives between individuals and plants enable us to increase nature connectedness, which is a better predictor of the pro‐environmental conservation behaviors we wish to facilitate (Richardson et al, 2016 ). Now may well be the time, a recent paper has identified that over the last decade public interest in plant‐related topics has increased, particularly with the advent of social media influencers, as such there may be a window of opportunity to develop an appreciation of plant science among the wider public, who to some degree are reconnecting with plants (Burke et al, 2022 ).…”
Section: Reversing the Extinction Of Botanical Education‐putting Plan...mentioning
confidence: 99%
“…Technology offers a considerable opportunity to engage people with plants [ 13 ] and one potential means of increasing the general engagement of people with plants that is straight-forward is the use of Smartphone Applications (hereafter apps). The number of people with smartphones has increased exponentially over the last few years with approximately 14.91 billion smartphones estimated to be in circulation in 2021 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%